DYNAMICS OF VALUE ORIENTATIONS OF STUDENTS OF THE STATE UNIVERSITY OF MANAGEMENT 2001-2018 - P. Tazov (Вестник университета)
The results of studies of value orientations of students of the State University of Management for the period 2001-2018 have been presented. Based on the analysis of the dynamics of values, a conclusion has been made about the peculiarities of the transformation of the value consciousness of the students of the State University of Management for the specified period. So, for students of the State University of Management, traditional value orientations are still very significant – the family, self-realization – the significance of these value orientations is increasing. At the same time, the results of a study in 2018 show the increasing importance of the values of “social altruism”.